SIRT4-Catalyzed Deacetylation of Axin1 Modulates the Wnt/β-Catenin Signaling Pathway - Wang, Yuting; Yue, Jicheng; Xiao, Mingzhe; Lu, Xiaomei; Chin, Yuen Eugene (Frontiers in Oncology, 2022)
Axin1 is a fundamental scaffolding protein of the destruction complex in the canonical Wnt signaling pathway, which plays a critical role in various biological processes. However, how Axin1 is regulated in activation of the canonical Wnt signaling pathway remains elusive. Here, we reported that Axin1 is constitutively acetylated in resting cells. Upon stimulation with Wnt, SIRT4 translocates from mitochondria to the cytoplasm and catalyzes Axin1 deacetylation, thus turning off the destruction complex. In this process, Lys147, a residue in the RGS domain of Axin1, plays a key role. We proved that the Axin1-K147R mutant results in exclusion of β-TrCP from the destruction complex, which leads to β-catenin accumulation even without Wnt stimulation. In summary, our work addressed a new model for better understanding the initial stage of the canonical Wnt signaling pathway in which SIRT4 translocates into the cytoplasm to deacetylate Axin1, which results in elimination of β-TrCP from the destruction complex.